Efficiency of implementation of state policy in the field of education on national upbringing - Valentyna Sahuichenko (Universidad de Cienfuegos, 2020)
The authors of the article approach the disclosure of the peculiarities of the functioning of educational institutions as an organization (macro-theoretical level) and the student's life world (meso- and micro-theoretical levels of philosophical and educational reflection) in the democratization of upbringing, including national education, which requires new management. The managerial and bureaucratic aspect of the functioning of educational institutions is closely related to their tasks as a formalized organization of the educational process and their material support, including control of improving efficiency and establishing links with other educational institutions, which is an important prerequisite for the development of education in democracy as governance inferior to other forms. The conclusions emphasize that in the life world of the educational institute there is also a professionalization of teachers, youth cultures and myths are formed.